A systematic review of contemporary phase I trials in patients with lymphoma. (December 2022) - Griguolo, G.; Zorzi, M.F.; Pirosa, M.C.; Treglia, G.; Bertoni, F.; Kuruvilla, J.; Zucca, E.; Stathis, A.
Abstract: We performed a systematic review of phase I trials specifically designed for lymphoma patients. PubMed and Cochrane Library databases were searched using (lymphoma*) AND (phase 1) and publication date 2015–2020 to identify phase I dose-finding trials including a majority of lymphoma patients. Eighty-two trials (n = 3289 lymphoma patients) were included: 46 (55%) enrolled only lymphoma patients, 34 (41%) included also other hematologic malignancies, 2 (2%) solid tumors. Forty-six trials (56%) evaluated a combination (in 25 addition of experimental drug to standard therapy). Seven trials (9%) enrolled untreated patients. Among trials reporting activity in lymphoma patients, 74% (n = 57) reported an overall response rate ≥ 30%. All trials reported grade ≥ 3 adverse events; however, rates were not comparable across trials. Thirty-one treatment-related deaths in lymphoma patients were reported (overall treatment-related grade 5 adverse events rate 0.94%). Phase I trials designed for lymphoma patients were generally safe and the majority reported overall response rate ≥ 30%. Graphical Abstract: ga1 Highlights: Phase I trials represent the first clinical evaluation of a new drug or combination. Several phase I trials have been designed specifically for lymphoma patients. We identified 82 trials (2015–2020) including a majority of lymphoma patients. These trials were overall safe, the majority reported an overall response rate≥ 30%. A greater degree of standardization in reporting safety results should be encouraged.